FAKTOR-FAKTOR PENYEBAB PERDARAHAN POSTPARTUM DI RSUD BANJARNEGARA TAHUN 2008 - Rosi Kurnia Sugiharti (Universitas Harapan Bangsa Purwokerto, 2009)
Background: Preliminary Survey conducted by researchers at the HospitalBanjarnegara, the incidence of postpartum hemorrhage in 2007 as many as 125and in 2008 142 mothers postpartum, so that the incidence of postpartumhemorrhage was increased by 11.97% in 2008 The cause of postpartumhemorrhage between another is atonic uterus, retained placenta, uterine inversio,rips through the birth canal and retained placenta. Objective: To determine the cause of the incident description of the factors ofpostpartum hemorrhage in Banjarnegara District Hospital in 2008. Based on anatonic uterus, retained placenta, uterine inversio, rips through the birth canal andretained placenta.Methods: This research method is quantitative descriptive based on secondarydata taken using a master table. The population of all postpartum mothersexperiencing postpartum haemorrhage in Banjarnegara District Hospital in 2008.Total population of 142 cases. The sampling technique using total sampling. Thetotal sample of 142.Results: Completeness of data in the medical record is only 142 PPH. atonicpostpartum hemorrhage because there were 11 cases (7.7%), retained placenta64 cases (45.1%), uterine inversio 0 cases (0%), birth canal laceration 20 cases(14.1%) and for the rest of the placenta There were 47 cases (33.1%).Conclusion: Overview of the causes of postpartum hemorrhage events inBanjarnegara District Hospital in 2008 among which atonic uterus, retainedplacenta, uterine inversion, rips through the birth canal and retained placenta.Keywords: Factors that cause, PPH